Successful implementation of interchange of biologic medications in chronic arthritis after information of costs to prescribers - Fernando Perez-Ruiz; Elena Garmendia-Sanchez; Javier Arostegui-Lavilla; Javier Duruelo-Echevarrieta; Joana Atxotegi-Saenz de Buruaga; Mayra Nathali Rivas-Zavaleta; Javier Casas-Arrate; Maria del Consuelo Modesto-Caballero; Amaya de Basagoiti-Gorordo (Exploration of Musculoskeletal Diseases, 2024)
Aim: To evaluate the impact of prescription, cost, and switching policy on the rate of switching from reference products to biosimilars. Methods: Analysis of an administrative database for prescription in a rheumatology division. Biosimilars for adalimumab and etanercept were available in 2019. Blinded costs and prescription data were not shared with prescribing physicians until 2021. The rate of prescription, persistence of therapy after switching, and reduction of cost were analyzed from 2019 to 2022. A new etanercept biosimilar was prioritized in 2022, and a new switching wave from biosimilar to biosimilar etanercept was implemented. Results: Overall switching from 2019 to 2022 comprised 132/135 (97.8%) of patients. The rate of switching increased from 13.3% to 34%, 79%, and 95.5% of patients on reference products during 2019, 2020, 2021, and 2022, respectively. In 2022, after sharing information, the switch comprised 55/135 (40.7%) of overall switching. The rate of persistence on therapy after switching was 86.8% for etanercept and 79.7 for adalimumab. During 2023, a rate of 76.6% switching etanercept reference-biosimilar-biosimilar was achieved. The reduction in the overall biologic budget in 2021 was 19.2% and 29.0% for the patient-year cost. Conclusions: Information to prescribers may improve switching policies. Persistence on biosimilar medications after switching is as high as previously reported.